Adaptive coping strategies of Ukrainians during the war - Гозак, Світлана; Єлізарова, Олена; Станкевич, Тетяна; Парац, Алла; Чорна, Валентина; Товкун, Лідія; Лебединець, Наталія; Бондар, Олександра (Psychosomatic Medicine and General Practice, 2023)
Abstract of the report "Adaptive coping strategies of Ukrainians during the war"